2023
DOI: 10.7717/peerj.14842
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycholic acid exacerbates intestinal inflammation by modulating interleukin-1β expression and tuft cell proportion in dextran sulfate sodium-induced murine colitis

Abstract: Background The etiology of inflammatory bowel disease (IBD) remains unclear. However, intestinal metabolism is known to be critical in the pathogenesis of IBD. Bile acid is one of the main intestinal metabolites, and its role in the pathogenesis of IBD is worthy of investigation. This study investigated the role of deoxycholic acid (DCA), a bile acid, in the pathogenesis of IBD. Methods Peripheral serum metabolomics, fecal metabolomics, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…Consistent with this, our research results also indicated that chlorfenapyr disrupted the balance between Th17 and Treg cells, leading to the development of intestinal inflammation. Moreover, deoxycholic acid, a secondary bile acid, was demonstrated to exacerbate intestinal inflammation in a dextran sulfate sodium (DSS)-induced colitis mouse model by modulating the expression of interleukin-1β and tuft cell proportion . Another study showed that elevation of deoxycholic acid could inhibit colonic epithelial wound healing, potentially through the activation of the nuclear bile acid receptor FXR and subsequent downregulation of CFTR expression and activity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, our research results also indicated that chlorfenapyr disrupted the balance between Th17 and Treg cells, leading to the development of intestinal inflammation. Moreover, deoxycholic acid, a secondary bile acid, was demonstrated to exacerbate intestinal inflammation in a dextran sulfate sodium (DSS)-induced colitis mouse model by modulating the expression of interleukin-1β and tuft cell proportion . Another study showed that elevation of deoxycholic acid could inhibit colonic epithelial wound healing, potentially through the activation of the nuclear bile acid receptor FXR and subsequent downregulation of CFTR expression and activity .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, deoxycholic acid, a secondary bile acid, was demonstrated to exacerbate intestinal inflammation in a dextran sulfate sodium (DSS)induced colitis mouse model by modulating the expression of interleukin-1β and tuft cell proportion. 69 Another study showed that elevation of deoxycholic acid could inhibit colonic epithelial wound healing, potentially through the activation of the nuclear bile acid receptor FXR and subsequent downregulation of CFTR expression and activity. 70 These findings suggested that deoxycholic acid might play a role in weakening the intestinal barrier function.…”
Section: Chlorfenapyr Induced Intestinal Inflammationmentioning
confidence: 99%
“…The following concentrations: 4 mM TCA, 4 mM GCA, 5 mM CA, 1.25 mM TCDCA, 1.25 mM GCDCA, 0.3125 mM CDCA, 0.6375 mM TDCA, 0.6375 mM GDCA, 0.3125 mM DCA, or 150 µM SDS, were then introduced and incubated at 37°C for 30 min. Following this incubation, bacteria were stained with 20 µM PI using previously described methods ( 10 , 11 ). Fluorescence of PI was measured using a TECAN INFINITE F200 (excitation = 560 nm, emission = 600 nm) and was normalized to the OD 600 of the culture prior to introduction of bile acids.…”
Section: Methodsmentioning
confidence: 99%
“…Bile acids also shape the gut microbiome’s composition due to their antimicrobial and detergent-like properties ( 4 ). Distinct changes to the bile acid pool and microbiome are associated with a wide variety of diseases including Clostridioides difficile infection (CDI) ( 10 ), inflammatory bowel disease ( 11 ), metabolic syndrome ( 12 ), and cancer ( 12 , 13 ). However, the mechanisms that dictate the bacterial-bile acid relationship are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“… 36 Deoxycholic acid aggravates intestinal inflammation via promoting the expression of IL-1β and the proportion of CD3 + and CD4 + T cells and reducing the number of tuft cells. 37 A consortium of Clostridium AP sp000509125, Bacteroides ovatus and Eubacterium limosum could produce secondary bile acids ursodeoxycholic acid and lithocholic acid to improve gut-barrier integrity in colitis mice. 38 Metabolite of tryptophan indole-3-propionic acid, which is decreased in UC and CD patients fecal, has the potential to restrain inflammation and fibrosis.…”
Section: Disease Pathogenesismentioning
confidence: 99%